DRD4 and DAT1 in ADHD: Functional neurobiology to pharmacogenetics - Darko Turic; James Swanson; Edmund Sonuga-Barke (Dove Medical Press, 2010)
Darko Turic1, James Swanson2, Edmund Sonuga-Barke1,31Institute for Disorders of Impulse and Attention, School of Psychology, University of Southampton, UK; 2Child Development Center, University of California, Irvine, California, US; 3Department of Experimental, Clinical and Health Psychology, Ghent University, BelgiumAbstract: Attention deficit/hyperactivity disorder (ADHD) is a common and potentially very impairing neuropsychiatric disorder of childhood. Statistical genetic studies of twins have shown ADHD to be highly heritable, with the combination of genes and gene by environment interactions accounting for around 80% of phenotypic variance. The initial molecular genetic studies where candidates were selected because of the efficacy of dopaminergic compounds in the treatment of ADHD were remarkably successful and provided strong evidence for the role of DRD4 and DAT1 variants in the pathogenesis of ADHD. However, the recent application of noncandidate gene strategies (eg, genome-wide association scans) has failed to identify additional genes with substantial genetic main effects, and the effects for DRD4 and DAT1 have not been replicated. This is the usual pattern observed for most other physical and mental disorders evaluated with current state-of-the-art methods. In this paper we discuss future strategies for genetic studies in ADHD, highlighting both the pitfalls and possible solutions relating to candidate gene studies, genome-wide studies, defining the phenotype, and statistical approaches.Keywords: dopamine, ADHD, pharmacogenetics, candidate gene